Pengembangan Ekowisata Berbasis Masyarakat dalam Perspektif Sustainable Livelihoods di Pemuteran Bali Utara - I Ketut Sardiana; I Made Sarjana (Universitas Udayana, 2021)
This study aims to analyze the development of Community Based Ecotourism (CBE) in Pemuteran Village, North Bali, in sustainable livelihoods (SL) perspective. The most interesting finding from this study is the central role of a social entrepreneur named Agung Prana who inspired the local community to build knowledge and practice of tourism. Coral reef restoration as the core of ecotourism development in Pemuteran Village. This initiative received broad support from stakeholders, marked by the establishment of local institutions and regulations that support environmental conservation and local economic development. This activity has succeeded in improving the quality of life and maintaining the sustainability of the livelihoods of the local community, despite the change in the focus of the development sector from agriculture to tourism.